PHYSICOCHEMICAL CHARACTERISTICS OF STARCH NOODLES BASED ON SORGHUM FLOUR (Sorghum bicolor L. Moench) AND SAGO FLOUR (Metroxylon Sp) - Marningsih Doko Patty; Erni Sofia Murtini; Widya Dwi Rukmi Putri (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2023)
Sorghum is one of the local commodities that has the potential to be developed into alternative food products. Sorghum is a gluten-free source of protein, vitamins, minerals and calories. This study aims to determine the effect of the proportion of sorghum flour and sago flour on physical and chemical characteristics and determine the best treatment for dry noodles. The experimental design used a completely randomised design with one factor, that is the proportion of sorghum flour and sago flour consisting of 6 levels (80:20; 75:25; 70:30; 65:35; 60:40; 55:45) grams. The results showed that the proportion of sorghum flour and sago flour affected the physical characteristics of colour, breakage, elongation, cooking time, cooking shrinkage, and water absorption, but had no effect on breaking point. The best behaviour was produced in the proportion of 60 grams of white sorghum flour and 40 grams of sago flour which was then chemically analysed to have a moisture content of 11.90%, fat content of 0.24, ash content of 1.15%, protein content of 5.98%, and carbohydrate content of 80.79%.